2011
DOI: 10.1007/s11418-011-0507-0
|View full text |Cite
|
Sign up to set email alerts
|

Compounds isolated from Curcuma aromatica Salisb. inhibit human P450 enzymes

Abstract: Curcuma species (Zingiberaceae) are used as both food and medicine in Asia. Ten sesquiterpenes (1-10) and two curcuminoids (11 and 12) were isolated from the rhizomes of Curcuma aromatica Salisb. and identified. The compounds were evaluated for their ability to inhibit cytochrome P450 (CYP). Among them, the sesquiterpene (4S,5S)-(+)-germacrone-4,5-epoxide (7) inhibited certain subtypes of CYP more potently than or at levels comparable to the curcuminoids curcumin (11) and demethoxycurcumin (12); 7 (IC(50) = 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 14 publications
3
23
1
Order By: Relevance
“…A third cause of adverse events is the inappropriate use of dietary supplements including an excessive intake or the concomitant use of various dietary supplements and/or medicines. In the past few decades, a large number of ingredients have been shown to interact with drugs [1521]; however, it currently remains unclear whether most ingredients in dietary supplements interact with drugs.…”
Section: Introductionmentioning
confidence: 99%
“…A third cause of adverse events is the inappropriate use of dietary supplements including an excessive intake or the concomitant use of various dietary supplements and/or medicines. In the past few decades, a large number of ingredients have been shown to interact with drugs [1521]; however, it currently remains unclear whether most ingredients in dietary supplements interact with drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Physicians and pharmacists need to be aware of which of their patients are concomitantly using dietary supplements and medicines because many herbs (e.g., black cohosh, coleus forskohlii, echinacea, garlic, ginkgo, ginseng, green tea, kava, milk thistle, and St. John's wort) 1318) and ingredients (e.g., catechins 19) , curcuminoids 20) , isoflavones 21) , quercetin 22) , and polyphenols 23) ) affect drug-metabolizing enzymes. Resveratrol 24) also affects the drug-metabolizing enzyme cytochrome P-450 (CYP).…”
Section: Introductionmentioning
confidence: 99%
“…The rhizome of Curcuma aromatica Salisb. is widely used as a traditional herbal medicine for anti-tumor therapy in China, Japan and other Asian countries (5). Findings of recent studies have demonstrated that germacrone, a major bioactive component of Curcuma aromatica Salisb., possesses anti-tumor, anti-inflammatory and neuroprotective properties.…”
Section: Introductionmentioning
confidence: 99%